Apprentice of graphic representation of a digital function to secondary cycle through activities done in group (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The intention behind this work based on a graphic representation of a function to secondary cycle, found a recurrent assumption of the difficulty felt by students reflected in bad marks along continued evaluations and in the national baccalaureate exam. The aim of this study is to get rid off the eventual causes of these difficulties and try to propose an effective teaching strategy for a good understanding of this part of lessons to students of 1st year baccalaureate experimental sciences. In this case we worked with group integrating technical activities on integration of limits and derivation. In this respect, we could unfold that the integration of these activities is interesting for a good understanding of graphic representation of a function, but this could not be efficacious only through applying an active didactic method â€œGroup working methodâ€ which does not only interests students of low level but also those of average ones, and high levels as well. Besides, this method is well appreciated by all students; they propose to generalise it on all subjects and lessons (Maths).